Urgensi Aspek Psikodermatologi dalam Perawatan Kulit: Memahami Keterkaitan Emosi dan Kesehatan Kulit - Bhakti Wiranti (PT. PENERBIT TIGA MUTIARA, 2024)
Skincare that focuses solely on the physical aspects often ignores the emotional impact that can significantly affect skin health. This review aims to examine the importance of psychodermatology in skincare, focusing on understanding the link between emotions and skin health. The study adopted a library research method focusing on integrative and comprehensive literature analysis to explore the interrelationship between psychodermatology and skincare. The results revealed that psychodermatology is crucial in detailing and addressing the dynamics of skin health and emotions. Involving the psychological dimension in skincare is a response to skin problems and a preventive measure that can positively impact an individual's skin and mental health. The findings highlight the influence of stress and emotions on skin health as a critical focus, as stress and emotional tension can trigger inflammatory responses that significantly affect skin conditions. Meanwhile, psychological interventions in skincare are emerging as innovative solutions that offer therapeutic approaches to help individuals manage stress, anxiety and self-image issues that may arise from skin conditions. Furthermore, the role of psychosocial factors in skin care confirms the importance of integrating self-image, appearance perception, and emotional support in designing treatment programs that focus on sustainability and overall well-being. Future studies should focus on identifying stressors that affect skin health and developing effective psychodermatology therapies for holistic skin care.